Synergistic Activation of VDR-RXR Heterodimers by Vitamin D and Rexinoids in Human Kidney and Brain Cells - Mobin Emran Doost; Jennifer Hong; Jennifer E. Broatch; Michael T. Applegate; Carl E. Wagner; Pamela A. Marshall; Peter W. Jurutka (Cells)
The active form of vitamin D, 1,25-dihydroxyvitamin D (1,25D), binds to the vitamin D receptor (VDR) with high affinity. The VDR then heterodimerizes with the retinoid X receptor (RXR) and associates with vitamin D response elements (VDREs) to regulate the transcription of target genes. Bexarotene (Bex) is an RXR ligand (rexinoid) developed to treat cutaneous T-cell lymphoma and is a putative therapeutic for other diseases. We postulate that VDR ligands (1,25D) and RXR ligands (Bex/analogs) can “synergize” to “super-activate” the VDR-RXR heterodimer. This “cross-talk” could allow disorders treated with high-dose Bex therapy (leading to significant adverse side effects) to instead be treated using both low-dose Bex and vitamin D. Thus, we designed experiments to examine the effect of both VDR and RXR ligands, alone and in combination, to activate VDR-RXR-mediated transcription. The goal was to determine if selected RXR-specific ligands can synergize with vitamin D to amplify RXR-VDR activity. The results demonstrate a synergistic effect with both Bex and 1,25D which could be further modulated by (1) the protein levels (or polymorphic version) of VDR present in the cell, (2) the concentration of the ligands, (3) the cellular “background” (e.g., brain cells versus kidney cells), (4) the nature of the VDRE platform, or (5) the type of rexinoid (Bex analogs). Our findings suggest that diseases that respond to treatment with either vitamin D, or with rexinoids, may be amenable to enhanced therapeutic potential by employing multi-ligand dosing via combinatorial therapy.